a. \(3\dfrac{1}{3}x+16=13,25\)
=> x + 16 = 13,25
=> x = 13,25 - 16
=> x = \(-\dfrac{11}{4}\)
b. x - 43 = (57 - x) - 50
=> 2x = 57 - 50 + 43
=> 2x = 7 + 43
=> 2x = 50
=> x = 50 : 2
=> x = 25
a, \(3\dfrac{1}{3}x\) + 16 = 13,25
\(\dfrac{10}{3}x\) + 16 = 13,25
\(\dfrac{10}{3}x\) = -2,75
x = -2,75 : \(\dfrac{10}{3}\)
x = -\(\dfrac{33}{40}\)
b, x - 43 = ( 57 - x ) - 50
x - 43 = 57 - x - 50
x + x = 57 - 50 + 43
2x = 50
x = 25
a,\(3\dfrac{1}{3}x+16=13,25\)
\(\Rightarrow\dfrac{10}{3}x+16=\dfrac{53}{4}\)
\(\Rightarrow\dfrac{10}{3}x=\dfrac{53}{4}-16\)
\(\Rightarrow\dfrac{10}{3}x=-\dfrac{11}{4}\)
\(\Rightarrow x=-\dfrac{11}{4}\div\dfrac{10}{3}\)
\(\Rightarrow x=-\dfrac{33}{40}\)
vậy x\(=-\dfrac{33}{40}\)